2012
DOI: 10.1136/neurintsurg-2011-010198
|View full text |Cite
|
Sign up to set email alerts
|

Angioarchitectural features associated with hemorrhagic presentation in pediatric cerebral arteriovenous malformations

Abstract: Background and objective To date, there have been few published studies examining the relationship between arteriovenous malformation (AVM) angioarchitecture and hemorrhagic presentation among children with cerebral AVMs. This study examines this relationship in this unique population, in whom symptomatic presentation of cerebral AVM is the norm rather than the exception. Methods A cohort of children with AVMs from 2000 to 2011 were included. Predictors studied included patient age, gender and angioarchitectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 31 publications
1
70
3
Order By: Relevance
“…28 Another report on 135 children with BAVMs indicated the presence of an association of exclusively deep venous drainage with hemorrhage. 25 The role of exclusively deep venous drainage should be analyzed in further studies with larger sample sizes by using standard angiographic methods, because only 9.3% of children with BAVMs had exclusively deep venous drainage in our study, which is much less than the 17%-28% rate reported in other studies. 7 The presence of an associated aneurysm and deep nidus location has failed to correlate with BAVM hemorrhage in all previous pediatric studies, and our data corroborate these findings.…”
Section: Bavm Hemorrhage Risk Predictors In Pediatric Patientscontrasting
confidence: 51%
See 3 more Smart Citations
“…28 Another report on 135 children with BAVMs indicated the presence of an association of exclusively deep venous drainage with hemorrhage. 25 The role of exclusively deep venous drainage should be analyzed in further studies with larger sample sizes by using standard angiographic methods, because only 9.3% of children with BAVMs had exclusively deep venous drainage in our study, which is much less than the 17%-28% rate reported in other studies. 7 The presence of an associated aneurysm and deep nidus location has failed to correlate with BAVM hemorrhage in all previous pediatric studies, and our data corroborate these findings.…”
Section: Bavm Hemorrhage Risk Predictors In Pediatric Patientscontrasting
confidence: 51%
“…24,26,28 Two larger studies reported results with a relatively distinct bias (a wide range of odds ratio or only radiosurgery patients), suggesting that these studies might have been underpowered to assess the impact of certain features on BAVM hemorrhage. 25,27 In this exclusively pediatric cohort (18 years old or younger) of patients with BAVMs referred to a high-volume Chinese neurosurgery center during the past 5 years, we identified periventricular nidus location and smaller nidus size as independent predictors of hemorrhagic presentation. In contrast to adult patients, deep location, exclusively deep venous drainage, and associated aneurysms were not significantly correlated with the appearance of hemorrhage in these children.…”
Section: Bavm Hemorrhage Risk Predictors In Pediatric Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11] Similar studies on AVM in children are, however, scarce and mostly based on studies from Europe and North America. 12,13 Whether those angiographic features that predict haemorrhage in Caucasian children with AVM similarly predict haemorrhage in Chinese children with AVM is unknown. The objective of this multicentre study was to determine specific angiographic factors associated with haemorrhagic presentation in brain AVM in the Hong Kong Chinese paediatric population, with a view to assisting clinical decision-making regarding the optimal timing and type of treatment.…”
Section: Introductionmentioning
confidence: 99%